Femmes et genre dans l’histoire de l’immigration. Naissance et cheminement d’un sujet de recherche - Linda Guerry (Genre & Histoire)
This article explores the existing historiography concerning women and gender in the history of immigration – seldom studied in France –, paying careful attention to the contextual and theoretical evolutions that marked the emergence of this topic in the humanities and social sciences. It begins with an analysis of the first studies within the social sciences before turning to those focused on women in immigration and then women's history in both France and the United States. In both countries this encounter took time and encountered difficulties. Finally, the article addresses the most recent work that integrates gender in the historical analysis of immigration.